(Un)equal Treatment? Elderly care and disability services for people with dementia in Finland. Issue 3 (September 2017) - Hoppania, Hanna-Kaisa; Mäki-Petäjä-Leinonen, Anna; Nikumaa, Henna
The rights of older people to care have become a major political and legal issue with the ageing populations of many European and OECD countries. Finland is an interesting case in this respect because in 2013, extensive new legislation was passed there concerning the rights of the older population to access care services. This article describes the context in which the 'Act on Supporting the Functional Capacity of the Older Population and on Social and Health Services for Older Persons' (980/2012 Elderly Care Act) was drafted, and what the Act aims to accomplish. It argues that while the Act is ambitious and symbolically significant, it remains unsatisfactory in practice. This is the case especially for people with dementia, who end up being disadvantaged. We compare the Elderly Care Act with other relevant legislation, in particular legislation pertaining to disability services, and estimate the significance of the law from the perspective of older people with dementia. We also discuss the situation in Finland in relation to the global situation of people with dementia as the UN Convention on the Rights of Persons with Disabilities was recently ratified in Finland. We show that disability legislation, rather than elderly care legislation, should be the framework through which the right to services should be secured for people with dementia.